2006
DOI: 10.1590/s0102-311x2006000400024
|View full text |Cite
|
Sign up to set email alerts
|

"The first shot": the context of first injection of illicit drugs, ongoing injecting practices, and hepatitis C infection in Rio de Janeiro, Brazil

Abstract: The context of first drug injection and its association with ongoing injecting practices and HCV (hepatitis C virus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
4
18
1
1
Order By: Relevance
“…The factors associated with HCV infection detected in illicit drug users in Breves are similar to those reported in epidemiological studies in different Brazilian municipalities for this risk group [3][4][5][6]11 . Specifi cally, the risk factors for HCV infection are identical to those detected in cocaine users in the State of Pará 11 , thus confi rming the local epidemiological profi le of HCV transmission in illicit drug users.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The factors associated with HCV infection detected in illicit drug users in Breves are similar to those reported in epidemiological studies in different Brazilian municipalities for this risk group [3][4][5][6]11 . Specifi cally, the risk factors for HCV infection are identical to those detected in cocaine users in the State of Pará 11 , thus confi rming the local epidemiological profi le of HCV transmission in illicit drug users.…”
supporting
confidence: 77%
“…In Brazil, epidemiological studies of HCV infection in illicit drug users are still rare. The prevalence of HCV infection in illicit drug users sampled in metropolitan areas in the Northeast, Midwest, South and Southeast regions of Brazil ranged from 5% to 36% [3][4][5][6][7] . There are frequent reports of clinical cases of hepatitis or pathologies associated with HCV infection in other population groups in northern Brazil [8][9][10][11] .…”
mentioning
confidence: 99%
“…It also corroborates findings from other international studies that the frequency of equipment sharing was higher at the first injection compared to current sharing habits, and that beginner PWID are frequently engaged in risky injecting behaviors. Studies elsewhere have established that PWID who had shared their injection equipment at the first injection were more likely to repeat this practice over the course of their injection career than those who had injected with new syringes (58.5% versus 16.5%; p = 0.003) [55,56]. Therefore, in Uganda where there is limited access to injecting equipment to cover all injections [16,57,58], the transitioning process becomes more complex and riskier.…”
Section: Discussionmentioning
confidence: 99%
“…In São Paulo, Silva et al (36) showed a prevalence of 41% among blood donors for this risk factor. Oliveira et al (29) and Smyth et al (37) showed an odds ratio for infection of ~3 for each 10-fold increase in the number of lifetime injecting episodes for those who shared needles/syringes compared to those who injected with sterile ones.…”
Section: Discussionmentioning
confidence: 99%